2020
DOI: 10.21203/rs.2.24034/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation between social media addiction and social media bullying: A cross sectional analytic study in Indonesian Youth

Abstract: BackgroundSocial media had eased communication among people in the last twenty years. However, the ease of being constantly connected also lead to problems, including social media addiction and social media bullying. Association between these two problems has not been researched extensively in Indonesia. Indonesia is the fourth most populous country in the world and said to be the most social media-addicted nation. Approximately 50% of the population is categorized as Youth Generation (Generation Y and Z) who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Although the research on attention span and DL is still under examination [56][57][58], it has been reported that multitasking (here defined as the ability to surf the internet and social media while in DL) has a direct effect on attention span [59] and can contribute to diminishing students' experience. The use of social media during DL requires further investigation, as uncontrolled usage of social apps can indeed produce the phenomenon of addiction, a decrement in social skills, and mental health disorders [60][61][62][63]. Education on device usage and netiquette [64] should be transversal and should include adolescents, teachers, and tutors.…”
Section: Sloveniamentioning
confidence: 99%
“…Although the research on attention span and DL is still under examination [56][57][58], it has been reported that multitasking (here defined as the ability to surf the internet and social media while in DL) has a direct effect on attention span [59] and can contribute to diminishing students' experience. The use of social media during DL requires further investigation, as uncontrolled usage of social apps can indeed produce the phenomenon of addiction, a decrement in social skills, and mental health disorders [60][61][62][63]. Education on device usage and netiquette [64] should be transversal and should include adolescents, teachers, and tutors.…”
Section: Sloveniamentioning
confidence: 99%